Incorporating Sustainability into Engineering and Chemical Education Using E-Learning - Edmond Sanganyado; Simbarashe Nkomo (MDPI AG, 2018)
The purpose of this study was to develop e-learning activities that could facilitate the integration of sustainability concepts and practices in engineering and chemical education. Using an online learning management system (LMS), undergraduate students in an applied chemistry program at a public university in Zimbabwe participated in an online discussion on the role of chemical reaction engineering in achieving environmental sustainability goals. In the second activity, the students were instructed to prepare a design report for a cost-effective and innovative wastewater treatment plant for a rural hospital. The design report was evaluated through peer review online. Quantitative and qualitative analyses were performed on the two online activities to evaluate student engagement, quality of responses and the incorporation of sustainability into their learning. In the online discussion, 97 comments were made averaging 120 words per comment. Furthermore, the students averaged 3.88 comments, with the majority of comments exhibiting simple and complex argumentation, a deep reflection and widespread use of terms associated with sustainability such as recycling, pollution, waste and the environment. Furthermore, the evaluation of peer reviews revealed that participants demonstrated they could identify the strengths and shortcomings in the design reports. Therefore, this study demonstrated that e-learning, particularly peer review and online discussion, could help chemistry and engineering students appreciate the need for chemical and engineering activities that encourage sustainable development.